1994
DOI: 10.1097/00004032-199402000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Natural Radioactivity in Spanish Soils

Abstract: The program of studies and surveys of natural radiation and radioactivity in Spain organized by our research group at the end of the 1980s included a 4-y national survey to determine the concentrations of natural radionuclides in soil. Results obtained from measurements of soil samples collected nationwide at > 900 sampling sites are reported and discussed in this paper. Correlations between absorbed dose rates in air calculated from natural radionuclide concentrations in soil and terrestrial gamma dose rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(52 citation statements)
references
References 0 publications
7
45
0
Order By: Relevance
“…Texture is silt loam and bulk density ranges between 1 and 1.2 g cm -3 . Table 1 shows the values of background levels of natural gamma radionuclides found in these profiles fall within the range for Spanish soils (Quindós et al, 1994) and also agree with values reported by Litaor (1995) and de Jong et al (1994) in North America.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Texture is silt loam and bulk density ranges between 1 and 1.2 g cm -3 . Table 1 shows the values of background levels of natural gamma radionuclides found in these profiles fall within the range for Spanish soils (Quindós et al, 1994) and also agree with values reported by Litaor (1995) and de Jong et al (1994) in North America.…”
Section: Resultssupporting
confidence: 86%
“…The methodology for determining natural gamma-emitting radionuclides is described by Quindós et al (1994). Soil samples were packed in 100 mL PVC cylindrical containers.…”
Section: The Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Such information is essential in understanding human exposure from natural and man-made sources of radiation and necessary in establishing rules and regulations relating to radiation protection [1].…”
Section: Introductionmentioning
confidence: 99%
“…These doses vary depending upon the concentrations of the natural radionuclides, 238 U, 232 Th, their daughter products and 40 K, present in the soils and rocks, which in turn depend upon the local geology of each region in the world [2,3].…”
Section: Introductionmentioning
confidence: 99%